Application and practice of the principles of Da 'wah in the age of globalization (2011)
Today despite the scientific and technological strides that have turned the world into a village, the long cherished values of a true traditional village life are rarely found in the prevailing global village. The fact seems to be that while human scientific and technological advancements have made life on earth more convenient and comfortable, it has failed to make it more decent, peaceful and sustainable. While studies abound on how the Islamic socioeconomic, political and ethical teachings can help re-direct the future of globalisation technologies towards a sustainable and peaceful world there are only few works on how the principles of Da‘wah intersect with such issues like multiculturalism, pluralism and inter-religious dialogue to build a more peaceful multicultural, multi-religious and equitable global society. This paper, therefore, examines how Da‘wah can be employed in promoting a global peace culture among the diverse groups in today’s world. The study discusses the involvement of Islamic organisations in inter-religious dialogues and situates it within the contemporary Islamic understanding of the Da‘wah principles and how these principles can help to militate against religious intolerance and the unwholesome effects of the prevailing cultural, religious and other clashes. The paper finally concludes that these Da‘wah principles are useful and desirable for improving upon and sustaining not only Muslim non-Muslim relations but also Muslim Muslim relations.